Reducing CSF complications by a recycled Hadad’s flap combined with autologous mucosa in secondary endoscope transsphenoidal surgery - Wang, Runfeng; Zhou, Gaoyang; Wang, Jin; Ma, Bo; Wang, Ping; Gao, Guodong; Sun, Shukai; Zhang, Zhiguo (Frontiers in Oncology, 2023)
Background: Transsphenoidal secondary operations are a minority but not a rare occurrence. How to viably prevent cerebral fluid (CSF)-related complications and confine surgery-caused injury in secondary surgery as minimally as possible is a huge challenge. This article shares our solution of recycling a prior Hadad-Bassagasteguy flap (HBF) along with a using small piece of free autologous mucosa to reconstruct the skull base.Methods: Of 69 patients, fitted criteria were assigned into 2 different groups: a recycled HBF incorporated with an autologous free mucosa and a recycled HBF incorporated with an artificial dura to rebuild the skull base in secondary transsphenoidal surgery.The postoperative morbidities of pseudomeningocele, CSF leakage and meningitis were recorded and analyzed.Results: A recycled HBF incorporated with an autologous mucosa is capable of reducing CSF complications compared to that of the matched group, particularly decreasing the morbidity of meningitis in secondary transsphenoidal surgery. Diabetes mellitus, craniopharyngioma, chordoma and the utilization of artificial dura were independent risk factors for CSF complications in secondary transsphenoidal surgery through univariate and multivariate logistic regression. In addition, diabetes mellitus and artificial dura are more likely to induce CSF leakage and meningitis. Patients suffering from craniopharyngioma are more susceptible to meningitis. Chordoma indiscriminately increased the risk of each CSF complication.Conclusions: A recycled HBF incorporated with an autologous mucosa is reliable for reconstructing the skull base in secondary transsphenoidal surgery, especially for patients simultaneously suffering from diabetes mellitus and central skull base tumors.